9 - A Recent Echo: African Private Higher Education in an International Perspective - Levy, Daniel C. (Journal of Higher Education in Africa, 2007)
Africa is a very recent arrival to the world scene of rapidly growing private higher education but it strongly echoes historical and contemporary patterns elsewhere. This is evident in each major category of analysis that merits our attention. It is evident in causes of growth, forms of growth, types of institutions, finance, gov- ernance, status, and roles played. Of course, such a broad generalization must not obscure significant differences and variation. Regions have their own salient char- acteristics and Africa is no exception. However, one does not adequately under- stand African private higher education without seeing it in a global context. In turn, the understanding of global context is enriched by incorporating Africa in the analysis.